Fasl and Wasl in al-Balaghah Research - Habibullah Khan; Adil Muhamed Al Akert (Journal of Islamic and Religious Studies, 2017)
Fasl and Wasl are the burning topics of ‘ilm ul-Bayan (Arabic Rhetoric) alongside it is very initial element which brings structure, beautification, embellishment and improvement. Many Arab scholars, in particular, Arab pioneer Rhetoricians had discussed and still have been discussing as well as discoursing Fasl and Wasl related matters. They put their all attention deeply to both of them in the discoursing of Qur’an structure. The utmost susceptible scholar Abu Bakr Abd al-Qahir bin ‘Abd arRahman bin Muhammad al-Jurjanī, the figurative personality, who first time in the history had discussed Fasl and Wasl based structures in his two prolific books; Asrar al-Balaghah (The Secrets of Elucidation) and Dala'il al-I’jaz (Intimations of Inimitability) theoretically and practically. Later on it was developed by Abu alQasim Mahmud bin ‘Umar al-Zamakhshari as he applied both theories to his commentary on Holy Qur’an known as “Al-Kashshaaf (the Revealer)”. The following research attempts all fruitful efforts spent by scholars having different ethics. It brings arguments towards where it is required, bringing out a short comparison between contemporary and classical Fasl and Wasl based perceptions resulting in what the scholar thinks in person.